TLR9 Signaling Protects Alcohol-Induced Hepatic Oxidative Stress but Worsens Liver Inflammation in Mice - Hao, Liuyi; Zhong, Wei; Sun, Xinguo; Zhou, Zhanxiang (Frontiers in Pharmacology, 2021)
Toll-Like Receptor 9 (TLR9) elicits cellular response to nucleic acids derived from pathogens or dead cells. Previous studies have shown that TLR9-driven response may lead to inflammation on the pathogenesis of liver diseases. This study aimed to determine how TLR9 mediates chronic alcohol exposure-induced liver pathogenesis by using TLR9 knockout (KO) mice. We observed that TLR9 KO mice were more susceptible to alcohol-induced liver injury, which was evidenced by higher serum ALT and AST levels and more hepatic lipid accumulation. Alcohol-induced oxidative stress and mitochondrial dysfunction were also exacerbated by TLR9 KO. We found that chronic alcohol exposure-induced hepatic CHOP and ATF6 activation were enhanced in TLR9 KO mice. Furthermore, alcohol-increased hepatic protein levels of Bim and cleaved caspase-3, two downstream targets of CHOP, were both enhanced by TLR9 KO. Using primary hepatocytes and AML-12 cells, we confirmed that TLR9 activation by CpG ODN administration significantly ameliorated acetaldehyde-induced ER stress, mitochondrial dysfunction, oxidative stress, and cell injury via suppressing the ATF6-CHOP signaling. Furthermore, we found that blocking TLR9-mediated STAT3 activation in AML12 cells inhibited ATF6-CHOP signaling cascade and thereby protecting against acetaldehyde-induced mitochondrial dysfunction and cell injury. Interestingly, we found that TRL9 KO mice ameliorated chronic alcohol exposure-induced CXCL1 induction and neutrophils infiltration in the liver. Furthermore, hepatocyte lack of STAT3 significantly ameliorated CpG ODN and LPS-increased CXCL1 levels. Overall, our data demonstrate that TLR9 signaling in hepatocytes counteracts alcohol-induced hepatotoxicity but worsens proinflammatory response.